A Comprehensive Analysis of Ariyah, Hibah, Hadiah, and Samsarah: Theoretical and Practical Perspectives - Karmila Karmila; Rufaidah Rufaidah; Haliza Nuriya; Zaitun Qamariah (Maslahah : Jurnal Manajemen dan Ekonomi Syariah, 2024)
This literature review article presents an analysis of the concepts of Ariyah, Grants, Gifts, and Samsarah from a theoretical and practical perspective to understand the complexity and legal framework governing these transactions in an Islamic context. The data is analyzed in depth to identify key elements and relationships between concepts. Ariyah (borrowing) is the loan of goods without remuneration, Hibah (grant) is the voluntary gift of a living person to another, Hadiah (gift) without expectation of reward, and Samsarah (brokerage) is connecting between parties involved in a transaction (such as buyers and sellers) in which the intermediary is given a certain commission. Despite having fundamental differences in definition and application, these four concepts play an important role in society. From a theoretical perspective, each concept has a legal basis and principles governing it. In practical terms, the application of Ariyah, Grants, Gifts, and Samsarah is seen in various aspects of daily life, from trade transactions to social relations. Understanding these concepts helps individuals and organizations manage relationships and transactions more effectively according to the principles of sharia law.